2004
DOI: 10.1023/b:ddas.0000037803.32013.aa
|View full text |Cite
|
Sign up to set email alerts
|

Tumor M2-Pyruvate Kinase, a New Metabolic Marker for Pancreatic Cancer

Abstract: An isoenzyme of pyruvate kinase (Tu M2-PK) is overexpressed by tumor cells and can be measured in blood by a specific immunoenzymatic assay. Our objective was to investigate the diagnostic value of Tu M2-PK in comparison with that of CA 19-9 in pancreatic cancer. We studied 265 subjects: 60 with histologically confirmed pancreatic cancer, 43 with benign pancreatic diseases (acute and chronic pancreatitis), 5 with benign cystic neoplasms of the pancreas, 9 with neuroendocrine tumors, 77 with other abdominal mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 5 publications
1
29
1
Order By: Relevance
“…6B). The K-rich regions possibly correspond to pancreatic cancer cells because K is a cofactor required to obtain maximum activity of the pyruvate kinase, an enzyme involved in glycolytic energy production, which has been observed in carcinoma tissue of the pancreas (31). The Gd as well as the Pt atoms located at those K-rich areas suggest the selective tumor accumulation of Gd-DTPA and DACHPt.…”
Section: Direct Detection and Treatment Of Pancreatic Cancermentioning
confidence: 99%
“…6B). The K-rich regions possibly correspond to pancreatic cancer cells because K is a cofactor required to obtain maximum activity of the pyruvate kinase, an enzyme involved in glycolytic energy production, which has been observed in carcinoma tissue of the pancreas (31). The Gd as well as the Pt atoms located at those K-rich areas suggest the selective tumor accumulation of Gd-DTPA and DACHPt.…”
Section: Direct Detection and Treatment Of Pancreatic Cancermentioning
confidence: 99%
“…The pyruvate kinase isoenzyme type M2 (M2-PK) is expressed in proliferating cells and tumour cells [87]. A study from Italy has shown that the blood levels of M2-PK had a sensitivity of 85% and specificity of 41% for the diagnosis of PC [88]. Our group is currently evaluating tumour M2-PK levels in stool of patients suffering from chronic pancreatitis and PC.…”
Section: M2-pkmentioning
confidence: 99%
“…Screening tests for the general population have to be accurate, safe, and convenient, as well as capable of high throughput. Many researchers have devoted considerable effort to discovering biomarkers of pancreatic cancer (8)(9)(10), and CA242 (11), M2-pyruvate kinase (12), PBF-4 (13), MIC-1 (14), PNA-binding glycoprotein (15), hTert (16), MMP-2 (17), and synuclein-g (18) have been reported as candidate biomarkers, but they were not clinically superior to CA19-9 or other clinical examinations.…”
Section: Introductionmentioning
confidence: 99%